Artificial light at night reduces larval survival and constrains female body mass in a capital breeding moth - Evert Van de Schoot; Renate A. Wesselingh; Hans Van Dyck (Basic and Applied Ecology)
Light pollution, caused by artificial light at night (ALAN), affects an ever-increasing area of the Earth and evidence is piling up on its negative effects on organisms, including insects. Besides direct sensory and physiological effects on adult behaviour, ALAN may also affect larval growth and developmental life cycle regulation (e.g., diapause induction). Moth species whose larvae are mainly diurnal may also be sensitive to the disruption of the day-night cycle by ALAN, but species with such an ecological profile remained understudied so far. The garden tiger moth Arctia caja mainly shows diurnal activity at the larval stages and adults are capital breeders that do not feed at all. In a split-brood rearing experiment, caterpillars of the F1 and F2 generation from wild-caught females were individually grown under either ALAN or control-dark conditions. We tested for constraints of ALAN on larval survival and development, and the consequences for body mass. We showed evidence for increased larval mortality under ALAN conditions in both the F1 and F2 generation. ALAN caused accelerated larval development by disturbing the induction of a feeding arrest (i.e., larval diapause). Pupal mass was lower under ALAN conditions, but only so in females. Capital breeders like A. caja are expected to be particularly affected by a decrease in female body mass since this will negatively affect fecundity and adult lifespan. Therefore, our results suggest that long-term exposure of moth populations to ALAN negatively affects capital breeding performance and hence population performance.